Fighting Poverty: International Experience and the Situation in Uzbekistan (Texas Journal of Multidisciplinary Studies, 2023)
An effective public economic policy aimed at correcting inequality is a key factor in the successful fight against poverty. If earlier the main problems of inequality were related to the countries at the lowest stage of economic development, now poor people are increasing in middle level countries. Both in Uzbekistan and in the whole world, socio-economic stratification, the gap between the "rich and the poor" has increased sharply again.